A Simple Numerical Method for Pricing an American Put Option - Beom Jin Kim; Yong-Ki Ma; Hi Jun Choe (Journal of Applied Mathematics)
We present a simple numerical method to find the optimal exercise boundary in an American put option. We formulate an intermediate function with the fixed free boundary that has Lipschitz character near optimal exercise boundary. Employing it, we can easily determine the optimal exercise boundary by solving a quadratic equation in time-recursive way. We also present several numerical results which illustrate a comparison to other methods.